Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1590/s0100-204x2018000500008
|View full text |Cite
|
Sign up to set email alerts
|

Heterosis in sweet sorghum

Abstract: The objective of this work was to evaluate the potential per se of male-sterile and fertility-restorer lines of sweet sorghum (Sorghum bicolor), as well as to detail the heterosis manifested for some traits directly or indirectly related to ethanol production, accumulation rate, and predictability. Evaluations were performed for 20 genotypes, of which 4 are fertility-restorer lines (R), 3 are male-sterile lines (A), and 12 are experimental hybrids (H) resulting from the partial diallel cross between lines A an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 13 publications
(14 reference statements)
1
2
0
Order By: Relevance
“…In the current study heterosis in productivity of green mass was caused by a simultaneous increase of plant height, stem diameter and plant foliage. This has been confirmed by the study of G. M. R. Lombardi et al [18].…”
Section: Resultssupporting
confidence: 63%
“…In the current study heterosis in productivity of green mass was caused by a simultaneous increase of plant height, stem diameter and plant foliage. This has been confirmed by the study of G. M. R. Lombardi et al [18].…”
Section: Resultssupporting
confidence: 63%
“…Thus, the heterosis observed in the analysis considering the parents and the hybrids in the present study is due to the epistatic effects and not to the effects of dominance, as expected. Lombardi et al (2018), Rocha (2016), and Durães (2014) in diallel studies on sorghum using the Griffing (1956) model, analyzing parents and F 1 s, also observed high phenotypic variance due to the effects of SCA for plant height and production of fresh biomass and verified the presence of nonadditive gene effects in the determination of these variables but treated them as due to the effects of dominance. Jiang et al (2017,) in more detailed studies of genetics in wheat, showed the importance of epistasis, mainly additive ´ additive in the heterosis calculation, in which it represented 50% of the genetic variation of heterosis, whereas the effects of dominance represented only 16% of the total variation.…”
Section: Resultsmentioning
confidence: 91%
“…In addition, it indicates that the average of the parentals for plant height is low and that the best of the parentals also has a small height. Lombardi et al (2018) and Singh & Shrotria (2008) reported heterosis and heterobeltiosis positive for plant height, with results of 3% to 52% heterosis for hybrids. The behavior of H% and Hb% of hybrids for plant height converge between works, indicating that, even in selecting shorter parentals, the heterotic gains must be considered to predict an increase in hybrids' height.…”
Section: Resultsmentioning
confidence: 96%